Pluralisme Agama dalam Islam: Study atas Pemikiran Pluralisme Said Aqiel Siradj - Zainal Abidin (Humaniora, 2014)
This work is motivated by the current phenomenon of that Muslims today strongly reject or even oppose to the concept of religious pluralism. To determine whether it is true or not that Islam rejects religious pluralism, Said Aqiel Siradj tries to see in a different way of pluralism itself, as in the fields of religion, politics, and socio-cultural. About pluralism in Islam, Said Aqiel Siradj shows that Islam can actually express themselves in a pluralistic religious world. Islam recognizes and judges pluralism critically, but Islam never refused or considered that pluralism is wrong. Pluralism is a fact of nature that can not be avoided. Islam would prefer to action that create prosperous of public, without the barriers of religion, ethnicity, race, and so on as the realization of Islam mission, rahmatan li al-'alamin, compassion for all creatures. This study uses hermeneutic approach. Methods that is used in collecting data is library research.